STUDY ON THE APPLICATION OF AUDIT FIRE MANAGEMENT SYSTEM IN RS X DISTRICT Y - Azriful iful Azriful; Hasbi Ibrahim; Herlina Herlina; Fatmawaty Mallapiang (Universitas Islam Negeri Alauddin Makassar, 2021)
Background: According to the Indonesian National Standard number 03-3985-2000, fire is a phenomenon that occurs when a material reaches a critical temperature and reacts chemically with oxygen to produce heat, flames, light, water vapor, carbon monoxide, or other products and effects. Fires are caused by various factors, either due to human factors or technical factors.Objective: This study aims to determine the application of fire management system audits in RS X Regency Y. Method:With a qualitative method through a case study approach.Determination of informants using the snowball method. Data collection was carried out by observation and in-depth interviews which were processed using content analysis, and triangulation of sources and methods was carried out.Result:The results showed that RS X had formed a fire organization by-laws and regulations, fire procedures did not run well when a fire broke out, and during the simulation, there were still technical obstacles when using fire tools.Conclusion:It is hoped that the management of X Regency Y Hospital will pay more attention to planning, training, and providing fire disaster preparedness.